OVERVIEW OF TRENDS IN FORMATION OF VENTURE SYSTEMS FOR INNOVATION FINANCING IN THE WORLD AND RUSSIA - A. G. Arakelyan (Финансы: теория и практика, 2017)
The international experience shows that venture capital investments are an effective way to develop scientific and technological progress and an essential element of national innovation systems. The importance of venture sector development is proved by the fact that most of the breakthrough innovations in high-tech industries are made by venture capital investments. Therefore, many developing countries, recognizing the importance of innovations, move towards supporting the process of commercialization of technological achievements. The Russian venture capital market has a number of features that distinguish it from the venture capital industry of other countries. However, the experience in the formation and development of the venture capital market in the U.S., Europe and Asia is still relevant for modern Russia. The international experience in establishing venture systems to fund innovations should be taken into account when forming the venture capital industry in Russia, with regard for peculiarities of the Russian economy, as well as based on the purposes in the area of innovation. The venture capital industry in developed countries is supported both at the legislative level and by the formation of a system of effective instruments of direct and indirect methods for stimulation of venture capital financing. The author investigated trends in development of venture systems in the world and Russia, found out specifics of formation of an effective venture capital industry in the USA, Europe and Asia and perspectives for innovative development in Russia.